PM2.5 exposure triggers cell death through lysosomal membrane permeabilization and leads to ferroptosis insensitivity via the autophagy dysfunction/p62-KEAP1-NRF2 activation in neuronal cells - Min Wei; Guangming Bao; Song Li; Zhaofei Yang; Cheng Cheng; Weidong Le (Ecotoxicology and Environmental Safety, 2022)
PM2.5 exposure can be associated with the onset of neurodegenerative diseases, with oxidative stress-induced cellular homeostasis disruption and cell death as one of the main mechanisms. However, the exact cellular and molecular processes are still rarely investigated. Autophagy and KEAP1-NRF2 (Kelch-like ECH-Associating protein 1-nuclear factor erythroid 2 related factor 2) signaling pathway are two main cellular defense systems for maintaining cellular homeostasis and resisting oxidative stress. In this study, we primarily investigated the role of autophagy and KEAP1-NRF2 in regulating cell death resulting from PM2.5 exposure in mouse neuroblastoma N2a cells. Our results showed that PM2.5 exposure disrupted autophagic flux by impairing lysosomal function, including lysosomal alkalinization, increased lysosome membrane permeabilization (LMP), and Cathepsin B release. Furthermore, dysregulated autophagy enhances NRF2 activity in a p62-dependent manner, which then initiates the expression of a series of antioxidant genes and increases cellular insensitivity to ferroptosis. Meanwhile, autophagy dysfunction impairs the intracellular degradation of ferroptosis related proteins such as GPX4 and ferritin. As these proteins accumulate, cells also become less sensitive to ferroptosis. LMP-associated cell death may be the main mechanism of PM2.5-induced N2a cytotoxicity. Our results may provide insights into the mechanisms of PM2.5-induced neurotoxicity and predict effective prevention and treatment strategies.